Cardiovascular mortality in liver and kidney transplant recipients: A retrospective analysis from a single institution. Issue 20 (21st May 2021) - Sertić, Zrinka; Letilović, Tomislav; Kanižaj, Tajana Filipec; Knotek, Mladen; Hadžibegović, Irzal; Starovečki, Inga; Jerkić, Helena
Abstract : Abstract: Previous studies have demonstrated cardiovascular causes to be among the leading causes of death after liver (LT) and kidney transplantation (KT). Although both recipient populations have unique pre-transplant cardiovascular burdens, they share similarities in post-transplant exposure to cardiovascular risk factors. The aim of this study was to compare cardiovascular mortality after LT and KT. We analyzed causes of death in 370 consecutive LT and 207 KT recipients from in-hospital records at a single tertiary transplant center. Cardiovascular causes of death were defined as cardiac arrest, heart failure, pulmonary embolism, or myocardial infarction. After a median follow-up of 36.5 months, infection was the most common cause of death in both cohorts, followed by cardiovascular causes in KT recipients and graft-related causes in LT recipients in whom cardiovascular causes were the third most common. Cumulative incidence curves for cardiovascular mortality computed with death from other causes as the competing risk were not significantly different ( P = .36). While 1-year cumulative cardiovascular mortality was similar (1.6% after LT and 1.5% after KT), the estimated 4-year probability was higher post-KT (3.8% vs. 1.6%). Significant pre-transplant risk factors for overall mortality after KT in multivariable analysis were age at transplantation, left ventricular ejection fraction <50%, and diastolic dysfunction grade 2 or greater, while significant risk factors for cardiovascular mortality were peripheral artery disease and left ventricular ejection fraction <50%. In the LT group no variables remained significant in a multivariable model for either overall or cardiovascular mortality. The present study found no significant overall difference in cardiovascular mortality after LT and KT. While LT and KT recipients may have similar early cardiovascular mortality, long-term risk is potentially lower after LT. Differing characteristics of cardiovascular death between these two patient populations should be further investigated.